Upaya Meningkatkan Kinerja Karyawan Melalui Pengelolaan Sumber Daya Manusia Pada (PT. Rabel Jasa Express) - Tuffahul Humairoh; Musayaroh Musayaroh; M. Zainal Alim; Iriani Ismail (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
PT. Rabel Jasa Express is a company engaged in the field of expeditions, this company has been operating for approximately 10 years and is located in Banyusangka, Tanjung Bumi, Bangkalan. The purpose of this research is to find out what efforts PT. Rabel Jasa Express to improve the performance of their employees. The research method we did was descriptive qualitative. We used 2 sources in collecting data, namely interviews and literature. The results obtained from this study are the efforts made by PT Rabel Jasa Express in improving HR management by creating a good work environment, giving awards to employees, and health insurance.